A low-cost Arduino-based datalogger with cellular modem and FTP communication for irrigation water use monitoring to enable access to CropManage. (October 2019) - Spinelli, Gerardo M.; Gottesman, Zach L.
Graphical abstract: Abstract: The Resource Conservation District of Santa Cruz County implemented a project to improve irrigation management through providing field assistance to growers. A web-based decision support tool called CropManage (https://v3.cropmanage.ucanr.edu ) developed by the University of California Cooperative Extension (UCCE) of Monterey County aids growers with irrigation scheduling. However, CropManage requires a flowmeter and a monitoring station to track water use in the field. In this article, we describe a device that was conceived as a low-cost alternative to Campbell Scientific flowmeter-monitoring stations that include data logger, modem, enclosure, battery, solar panel and charge regulator and cost above $2000. The device was designed for low-cost, ease of construction and with the capability of emulating the Campbell Scientific equipment functions and outputs. The devices were enabled with FTP communication to a central FTP server and were built with an Arduino MEGA, an Adafruit Datalogging Shield and an Adafruit FONA cellular modem. A voltage divider was added to monitor the external 12 V battery voltage and a DC/DC converter was used to convert 12 V to 5 V. Each field station, including the device, battery, enclosure and solar panel has a total cost below $300, while the FTP server costs less than $100. The device was tested for two years in filed conditions and gave output equivalent to the Campbell Scientific equipment. The device is a low-cost technology that enables growers to gain access to CropManage cheaply and reliably.